Cultural and Political Resistance Strategies of Black Women in Murindó, Antioquia (Colombia) - Valoyes Cabrera, Yuliza (2020)
This article is the result of theoretical investigation and field research work, which tries to understandthe struggle and resistance processes Afro-colombian women in the community of Murindó-Antioquia, to co-exist and re-establish themselves in their territory amid the logistics imposedby armed groups and their violence. This allows us to understand, then, the central and upliftingrole they play within their community. The methods of resisting in this female-led community arestrategic and outside the norm, in their commitment to living in decent conditions, preserving theirways of being and existing in the world, from a cultural and ancestral worldview of their own.